Artistic Research in the Process of Documentary Filmmaking Semua Pasti Bertuan - M. Kisra Anusyirwan; Citra Dewi Utami; Nur Rahmat Ardi Candra Dwi Atmaja (Gondang: Jurnal Seni dan Budaya, 2025)
Documentary filmmaking serves as a potent medium for both social advocacy and artistic expression, particularly when highlighting environmental urgencies. This study investigates the implementation of artistic research in the creation process of the documentary film Semua Pasti Bertuan, which addresses the critical issue of plastic waste management. Artistic research provides a systematic framework ensuring that every cinematic element is constructed based on deep findings and critical reflections conducted throughout the production process. This comprehensive approach effectively bridges the gap between conceptual theory and practical execution across all production phases. In the pre-production phase, ideas were developed through rigorous direct observation of the environment and by scouting subjects suitable for the theme to ensure strong narrative relevance. The production phase executed a participatory documentary approach, significantly employing the Informal Conversational Interview Method using Direct Recording Techniques on Subjects Engaged in Activities, alongside planned camera movement techniques to maintain visual authenticity. This specific interview technique was essential for capturing spontaneous, genuine responses without disrupting the subjects' daily routines. Furthermore, in the post-production phase, background music selection, Lower Third Placement Strategy, and the utilization of project documentation served as strategic narrative tools to strengthen the film's message delivery and emotional impact. The results indicate that artistic research plays a pivotal role in enriching the filmmaker's understanding before making creative decisions. Ultimately, this study concludes that integrating a structured artistic research methodology enables a more profound exploration of complex subject matter, resulting in a documentary that is both aesthetically compelling and socially resonant.